Trimethylamine-N-oxide (TMAO) increased aquaporin-2 expression in spontaneously hypertensive rats. (19th May 2019) - Liu, Min; Han, Qinghua; Yang, Jinglu
ABSTRACT: Recent evidence suggests that elevated plasma levels of Trimethylamine-N-oxide (TMAO) can prolong the duration of elevated blood pressure in rats. The purpose of this study was to investigate the plasma TMAO level in Spontaneously Hypertensive Rats (SHR) and to explore the possible relationship between TMAO and aquaporin-2 (AQP-2) in the formation of hypertension. Twelve-week-old, male Spontaneously Hypertensive rats (SHR, n = 40) and Wistar-Kyoto rats (WKY, n = 40) were accordingly grouped into SHR group and WKY group. Each group was divided randomly into four subgroups: Untreated group, TMAO group, TMAO+Tolvaptan (TMAO+TVP) group, and TVP group, respectively. Systolic blood pressure (SBP), plasma TMAO, plasma osmolality (POsm), plasma vasopressin (PAVP), and plasma AQP-2 (PAQP-2) concentration were measured, and the expression of AQP-2 in kidney medulla was detected by RT-PCR and Western blot. At 14 weeks, rats in SHR TMAO group were shown the increased plasma TMAO, POsm, PAVP, and PAQP-2 levels, while those rats in SHR TMAO+TVP group were shown the decreased plasma TMAO, POsm, and PAQP-2 levels, but an even higher PAVP (due to the blockage of TVP to V2 receptor). These findings indicate that an increase of plasma TMAO levels in SHR leads to a higher plasma osmotic pressure, triggers the regulation of the TMAO-AVP-AQP-2 axis in SHR, elicits the greater water reabsorption, and eventually leads to hypertension.